Primary sequence and location of the idiotopes of V-88, a DNA-binding monoclonal autoantibody, determined by idiotope scanning with synthetic peptides on pins. - Staines, N A (1993)
In this study, the primary sequence and location of the idiotopes of monoclonal antibody (mAb) V-88 have been examined. V-88 was derived from an adult (NZB x NZW)F1 mouse, has been partially defined previously with polyclonal anti-idiotype antisera, and is a member of the 16/6 idiotype (Id) family. From the inferred primary amino acid sequence of the antibody, sets of hexapeptides, overlapping by five residues, were synthesized on pins and used to scan the expression of epitopes (idiotopes) in the V regions of the light and heavy chains. A heterologous rabbit antiserum raised against the native antibody V-88, and absorbed to make it idiotype specific, was found to react with eight major epitopes distributed between the VH and VL regions. Half of these determinants mapped to the complementarity determining regions, with the others in framework sequences. Thus, the idiotype of antibody V-88 comprises, at least in part, continuous linear idiotopes in both hypervariable and framework areas. The process of absorbing the anti-idiotype antiserum on normal mouse immunoglobulin removed much of the background antibody activity against V region peptides, but left the activity against the dominant idiotopes. The sequence of a major idiotope, VATISG, in the FW2/CDR2 VH region is homologous to sequences of human antibodies that express the 16/6 idiotype, suggesting that Id.16/6 is at least in part defined by this region of the antibody. The same VH area is also homologous to sequences in bacterial and mammalian heat-shock proteins (hsp60-65). Thus there may be a functional link through idiotype connections, especially those involving Id.16/6, between anti-bacterial responses and production of autoantibodies, and some bacterial antigens may function indirectly as superantigens for B cells.